2018
DOI: 10.1016/j.simyco.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Novel and interesting Ophiocordyceps spp. (Ophiocordycipitaceae, Hypocreales) with superficial perithecia from Thailand

Abstract: Ophiocordyceps is a heterogeneous, species-rich genus in the order Hypocreales (Sordariomycetes, Ascomycota) that includes invertebrate-pathogenic taxa. In this study, seven new species in Ophiocordyceps producing superficial perithecia infecting various insect hosts (Lepidoptera, Hemiptera) are described from Thailand – Ophiocordyceps brunneinigra, O. brunneiperitheciata, O. geometridicola, O. multiperitheciata, O. pauciovoperitheciata, O. pseudoacicularis and O. spataforae. Phylogenetic analyses based on mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 47 publications
0
34
0
Order By: Relevance
“…Ophiocordycepsmacroacicularis S. Ban et al was introduced by Ban et al (2015) and was recently recorded from Thailand by Luangsa-ard et al (2018) based on molecular phylogeny together with morphology (Figs 2, 4). To the best of our knowledge, this is the first record of O.macroacicularis in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Ophiocordycepsmacroacicularis S. Ban et al was introduced by Ban et al (2015) and was recently recorded from Thailand by Luangsa-ard et al (2018) based on molecular phylogeny together with morphology (Figs 2, 4). To the best of our knowledge, this is the first record of O.macroacicularis in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…Collected specimens were stored in plastic boxes, returned to the laboratory, and examined under a stereo microscope (Olympus SZ61). Isolation from the teleomorphs followed the method described by Luangsa-ard et al (2018).…”
Section: Fungal Materials and Isolationmentioning
confidence: 99%
“…Cryptic species refers to taxa that are morphologically similar, yet evidence has shown that they are on different evolutionary paths as revealed by molecular phylogenetic methods and can only be recognized by their DNA sequences. Entomopathogenic fungi from Thailand are commonly encountered in the forests and constitute a huge number in our collections (Kobmoo et al 2012;Luangsa-ard et al 2018;Mongkolsamrit et al 2018;Tasanathai et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The water agar medium was also used to visualize the mycelial growth of the isolated fungus ( Figure 2E). The morphotaxonomic characteristics of conidia-forming mycelia and conidia structure were identified [22,23].…”
Section: Isolation and Identification Of Fungal Isolatementioning
confidence: 99%